2008
DOI: 10.31420/uakari.v2i1.13
|View full text |Cite
|
Sign up to set email alerts
|

DENSIDADES DE PIRARUCU (<i>Arapaima gigas</i>, TELEOSTEI, OSTEOGLOSSIDAE) EM LAGOS DAS RESERVAS DE DESENVOLVIMENTO SUSTENTÁVEL MAMIRAUÁ E AMANÃ, AMAZONAS, BRASIL

Abstract: At the Sustainable Development Reserves of Mamirauá and Amanã, the pirarucu fishery is co-managed. Local fishermen assess pirarucu populations and, with the help of the Mamirauá Institute and state government, use this information to establish fishing quotas. Surveys are possible by counts of individual coming to the surface to breath air. This study reports preliminary findings of pirarucu population densities in the areas within the reserves based on the time series built in the last years and on satellite i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 0 publications
2
22
0
4
Order By: Relevance
“…Previous detailed descriptions of the procedures used in censusing arapaima populations have shown that the count data for arapaima in Jarauá are relatively reliable (Castello 2004;Castello et al 2009Castello et al , 2011. Count data were collected by local fishers who had their counts validated by concurrent total seine catches or markrecapture estimates of abundance (Arantes et al 2006Castello 2004). Also, the Mamirauá Institute monitors the accuracy of the counts through the use of field observers and crosschecks of counts in certain lakes.…”
Section: Data Sources and Interpretationsmentioning
confidence: 99%
“…Previous detailed descriptions of the procedures used in censusing arapaima populations have shown that the count data for arapaima in Jarauá are relatively reliable (Castello 2004;Castello et al 2009Castello et al , 2011. Count data were collected by local fishers who had their counts validated by concurrent total seine catches or markrecapture estimates of abundance (Arantes et al 2006Castello 2004). Also, the Mamirauá Institute monitors the accuracy of the counts through the use of field observers and crosschecks of counts in certain lakes.…”
Section: Data Sources and Interpretationsmentioning
confidence: 99%
“…The várzeas floodplains of the Amazon River constitute the largest flooded forest system within the Amazon basin, covering a total area of approximately 200 million hectares [32]. The Mamirauá Reserve represents one of the largest portions of the várzea, with high densities of arapaimas, reaching in some lakes more than 1,000 adults per square kilometer [33], [8]. The conservation of these environments may be reinforcing this refuge effect, given that the Unini and Auati-Paraná Extractivist Reserves, Mamirauá and Amanã Sustainable Development Reserves, together with the Jaú National Park, form a contiguous protected area of almost six thousand hectares.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, measures have been taken to ensure the conservation of this resource, which include the managed fishery of stocks in sustainable use protected areas, such as the Mamirauá Sustainable Development Reserve (RDSM), Amazonas, Brazil [6], [7]. Participative management has been developed in this conservation unit since 1992, producing satisfactory results, which include an increase in arapaima’s density [8], while the number of fishermen has also increased, along with their gross income [7].…”
Section: Introductionmentioning
confidence: 99%
“…), curimatã, aruanã, tucunaré, pacu, bodó, pirapitinga (Piaractus brachypomus) tambaqui and pirarucu; with the exception of jaraqui all others are caught in lakes (Barthem 1999;Viana 2004) and would thus be subjected to more intense regional fishing pressure. Some studies show that the fishing-management measures (including the zoning systems of lakes) adopted in Mamirauá have been successful to enhance the populations of pirarucu (Arantes et al 2005) and tambaqui (Costa et al 1999), but possible management effects on the whole fish community are not yet well known. Some studies show that the fishing-management measures (including the zoning systems of lakes) adopted in Mamirauá have been successful to enhance the populations of pirarucu (Arantes et al 2005) and tambaqui (Costa et al 1999), but possible management effects on the whole fish community are not yet well known.…”
Section: Study Areamentioning
confidence: 99%